2020
DOI: 10.3390/pharmaceutics12121143
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 2 (BMP-2) Aggregates Can be Solubilized by Albumin—Investigation of BMP-2 Aggregation by Light Scattering and Electrophoresis

Abstract: Bone morphogenetic protein 2 (BMP-2) has a high tendency to aggregate at physiological pH and physiological ionic strength, which can complicate the development of growth factor delivery systems. The aggregation behavior in differently concentrated BMP-2 solutions was investigated using dynamic and static light scattering. It was found that at higher concentrations larger aggregates are formed, whose size decreases again with increasing dilution. A solubilizing effect and therefore less aggregation was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…Tween 20 and BSA apparently had a solubilizing effect on BMP-2 and prevented its precipitation at pH 7.2. Previous studies have shown that albumin influences the size of BMP-2 aggregates [ 23 ]. It was also found that BMP-2 still largely remained in the form of redissolvable aggregates despite the addition of BSA and Tween 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tween 20 and BSA apparently had a solubilizing effect on BMP-2 and prevented its precipitation at pH 7.2. Previous studies have shown that albumin influences the size of BMP-2 aggregates [ 23 ]. It was also found that BMP-2 still largely remained in the form of redissolvable aggregates despite the addition of BSA and Tween 20.…”
Section: Discussionmentioning
confidence: 99%
“… Schematic presentation of the proposed effect of chitosan on the aggregation tendency of BMP-2. Left (without chitosan): Ionic BMP-2 self-interaction, leading to BMP-2 aggregation [ 23 ]. Right: Binding of chitosan to the negatively charged tips of BMP-2 [ 27 ], potentially leading to a decreased aggregation tendency.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что BMPs, в частности BMP-2, имеет высокую склонность к агрегации при физиологических pH, что может усложнить разработку систем доставки данных белков [21]. Как правило, образование антител происходит либо зависимым от Т-клеток, либо независимым от Т-клеток образом.…”
Section: белковые агрегатыunclassified
“…The method was proposed as a simple, rapid, and economical alternative to LC-based approaches. Additional methods were also developed for analyzing the charge heterogeneity and aggregation/solubility of cytokines [113,114].…”
Section: Analysis Of New Modality Protein Therapeuticsmentioning
confidence: 99%